Climate variability and dynamics of precipitation distribution in Haryana, India - Rajesh Kumar; Mehtab Singh (National Geographical Journal of India, 2022)
Global climatic indicators are indicating rapidly changing climatic conditions at the global level. By taking 1850-1900, the IPCC is estimating a warming of about 1.50C in global surface temperature in comparison to the climatic conditions of pre-industrial revolution. Not only the global average surface temperature is continuously increasing but also the number of extreme events. The variability in climatic parameters poses great risk for the farming community at the global level in general and specific in semi-arid areas such as Haryana in particular. The present research work emphasis on the assessment of climatic variability and anomalies in the distribution of rainfall at micro level.